Moj svet pun svetlosti . My World Full of Lightness - Acin, Andrej (Serbia and Montenegro, 2007)
Donation from OSI-Budapest Arts and Culture Program. Duration: 00:50:00 In the 1950s two boys from village Ratkovo, Yugoslavia dreamt about building a cinema. Although they didn't know anything about film history, technology or the art of movie making, together they designed a projector and started making their own films. The film tells the story of the projector made of wood, films made of paper and glued together with dough. A historian from the Yugoslav Film Archives claims that the objects constructed and created by Milomir Bojovic and Lazar Aleksic should be placed at the Archive.